Liang-Ge-San, a Classic Traditional Chinese Medicine Formula, Attenuates Lipopolysaccharide-Induced Acute Lung Injury Through Up-Regulating miR-21 - Yang, Huayi; Lu, Zibin; Huo, Chuying; Chen, Yuyao; Cao, Huihui; Xie, Pei; Zhou, Hongling; Liu, Dongyi; Liu, Junshan; Yu, Linzhong (Frontiers in Pharmacology, 2019)
Background: Acute lung injury (ALI) is a life-threatening disease without effective chemotherapy at present. Liang-Ge-San (LGS) is a famous traditional Chinese medicine formula, which is used to treat ALI in China. However, only a few studies have addressed the mechanisms of LGS in ALI. Purpose: To evaluate the anti-inflammatory effects of LGS on lipopolysaccharide (LPS)-induced ALI, and to explore its underlying molecular mechanism. Methods: Murine RAW264.7 cells were treated with LGS and LPS (1 μg/ml). The generation of IL-6, TNF-α, IL-1β and IL-4 was detected by ELISA. The protein expressions of STAT3 and P-STAT3 (Tyr705) were determined by Western blotting and fluorescence confocal microscopy. STAT3 transcriptional activity was investigated by luciferase reporter gene assay. qPCR was used to detect the expressions of microRNA-21 (miR-21), STAT3 and IL-6. DSS cross-linking assay was used to assess the change of STAT3 dimer. In vivo anti-inflammatory effects of LGS were evaluated in an ALI mouse model induced by tracheal instillation of LPS (3 mg/kg). The anti-ALI effects were evaluated by ELISA, qPCR, Western blotting, BCA and H&E assays. Results: LGS suppressed LPS-stimulated IL-6, TNF-α and IL-1β generation, increase the generation of IL-4 in murine macrophages RAW264.7. Moreover, LGS down-regulated protein levels of P-STAT3 (Tyr705) and STAT3, inhibited STAT3 transcriptional activity, and up-regulated miR-21. Furthermore, blockage of miR-21 antagonized the inhibitory effects of LGS on the production of IL-6 and the expressions of P-STAT3 (Tyr705) and STAT3 as well as the formation of STAT3 dimer. Critically, LGS up-regulated the expression of miR-21 and inhibited the protein expressions of STAT3 and P-STAT3 (Tyr705) to reduce the release of IL-6 and inflammatory cell infiltration as well as the degree of edema in LPS-induced ALI mice. Conclusion: LGS inhibited LPS-induced ALI through up-regulating miR-21 and subsequently inhibiting the STAT3 signaling pathway, thereby decreasing the release of IL-6.